Efficacy of Alendronate in Preventing Periprosthetic Bone Loss after Implantation of a Primary Hip Endoprosthesis - Shabani, Ilir; Samardjiski, Milan; Kamnar, Viktor; Atanasov, Nenad; Bogojevska Doksevska, Milena; Popovska, Danica; Belchishta, Anila (Scientific Foundation SPIROSKI, 2022)
BACKGROUND: Total hip arthroplasty (THA) is now the gold standard for the surgical treatment of coxarthrosis. The appearance of bone loss after implantation of the hip endoprosthesis over time reduces the primary stability of the implant and leads to progressive loosening of the implant or periprosthetic fracture, which are considered to be the most common causes of hip revision. AIM: The aim of this study is to evaluate the value of alendronate application in reducing periprosthetic osteolysis reduction after implantation of total cementless hip endoprosthesis. METHODS: The study analyzed 50 patients operated on with implantation of a cementless THA. The first group of 25 patients received oral alendronate, calcium, and Vitamin D3 postoperatively. The second group of 25 patients was examined and followed postoperatively without any therapy. Patients were examined by RTG and dual energy X-ray absorption (DXA) methods at 6, 12, and 18 months. RESULTS: The study showed a difference in the values of bone mineral density and bone mineral content in the interval of 6,12, and 18 months, using the DXA method. CONCLUSION: Alendronate therapy after total hip implantation reduces periprosthetic bone loss, maintains bone mineralization, and strengthens the implant.
Keywords: Total hip arthroplasty; Alendronate therapy; Dual energy X-ray absorption